Pengaruh Brand Ambassador, Harga dan Kualitas Produk Terhadap Keputusan Pembelian Chitato (Survei pada Komunitas Carat Solo) - Putri Cahyani; Sumaryanto (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study was designed to empirically test the significance of the influence of brand ambassadors (X₁), price (X₂), and product quality (X₃) on the purchase decision (Y) of Chitato products among the Carat community in Solo. The methodology used was a quantitative survey of 100 respondents selected using purposive sampling. The data were analysed using multiple linear regression after passing validity, reliability, and classical assumption tests. The results of the study concluded as follows: (1) The regression equation formed is Y = -1.935 + 0.258X₁ + 0.281X₂ + 0.394X₃ + e. (2) Partially, the t-test confirmed that brand ambassadors, price, and product quality had a significant effect on purchasing decisions. (3) Simultaneously, the F test shows that the regression model is significant. (4) The coefficient of determination (Adjusted R2) is 61.4%, which means that the simultaneous contribution of the three independent variables to the dependent variable is 61.4%, while the remaining 38.6% is influenced by other variables outside the model.